Multifaces of the body: perceptions about body image throughout life cycles - Amaral, Sandy Souza do; Arruda, Amália Gonçalves; Barbosa, Elane da Silva; Fernandes, Helder Matheus Alves; Silva, Amanda Sângela de Oliveira (O Mundo da Saúde, 2023)
The meanings attributed to the body are commonly related to its limitation of being born, living and dying. Given this, these conceptions cross all the individual's generational cycles, from before birth, in the symbiosis of the mother-child binomial, until death. Therefore, there is a limitation of bodily understanding in its entirety and the perpetuation of misinformation. In this sense, the study aims to assimilate perceptions about body image throughout life cycles. The qualitative approach of a comparative and narrative study of multiple cases was adopted, the research setting was a basic health unit in the municipality of Aracati/CE, located on the east coast. The population was stratified into four groups: childhood, adolescence, adulthood and old age. Next, the sample was selected by choosing two individuals, a male and a female, from each age group. The implementation of the four workshops took place between September and November 2021, based on the dynamics of sensitivity and creativity of the sensitive creative method, based on the ideas of problematizing education by Paulo Freire. The analysis was carried out using the Pêcheux Discourse Analysis technique. During this study, it was noticed that the body undergoes changing representations of signs and symbols over the generations. Throughout the research, the identification of body image was reflected in the recent and stored experiences of each individual. Therefore, the contribution of this investigation to the performance of health professionals refers to the fact that communication is fundamental in the relationship between professional and client.